Multicultural and Religious Values in Senior High School (SMAN 1) Tegaldlimo Banyuwangi - Novi Hardaning Tiyas (IJIE International Journal of Islamic Education, 2022)
All school residents apply multicultural education values in schools to create a sense of tolerance and respect for students' culture, religion, ethnicity, and economy. It would be nice if the values of multicultural education could be applied through religious culture in schools so that we can know the habituations made by all school residents at senior high school (SMAN 1) Tegaldlimo Banyuwangi. This research uses descriptive qualitative research type of field research. The results of this study are: 1) Building the mutual trust of students through religious culture, namely through a culture of habituation to learning in the classroom and direct learning in schools. 2) Maintain a mutual understanding of students through religious cultures, such as charitable activities that can foster an attitude of cooperation and mutual understanding because they want to help their friends in distress. 3) Upholding the attitude of mutual respect for students through gathering activities at the homes of friends or teachers carrying out holidays and the culture of implementing Sapa, Salim, Salam, Senyum, Sopan (5S) to uphold the attitude of cooperation between students at this State Senior High School.